2023
DOI: 10.1007/s12032-023-01993-z
|View full text |Cite
|
Sign up to set email alerts
|

BRAF inhibitors in BRAF V600E-mutated ameloblastoma: systematic review of rare cases in the literature

Abstract: Background Ameloblastoma in 66% of the cases harbor a somatic mutation of the “mitogen-activated protein kinase” signaling pathway (BRAF V600E). In V600E mutations, BRAF is in the permanent “on” state and relays the growth-promoting signals independently of the EGFR pathway. Therefore, mutant BRAF represents a target for handful of new drugs. Methods We conducted a literature search, with the search terms “Vemurafenib, Dabrafenib, Ameloblastoma, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similar case studies presented remarkable downsizing of the BRAF -mutated ameloblastoma or metastatic ameloblastoma after receiving therapies with different doses of BRAF -inhibitors or combined BRAF - MEK -inhibitors [ [11] , [12] , [13] ]. Even a case of metastasized ameloblastoma responding remarkably well to BRAF/MEK inhibitor therapy has been documented ion the literature and underscores the clinical utility of neoadjuvant therapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar case studies presented remarkable downsizing of the BRAF -mutated ameloblastoma or metastatic ameloblastoma after receiving therapies with different doses of BRAF -inhibitors or combined BRAF - MEK -inhibitors [ [11] , [12] , [13] ]. Even a case of metastasized ameloblastoma responding remarkably well to BRAF/MEK inhibitor therapy has been documented ion the literature and underscores the clinical utility of neoadjuvant therapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6 Patients with ameloblastoma that displays BRAF mutations are potentially eligible for targeted therapy using MAPK pathway (BRAF, MEK, ERK) inhibitors. 7 For this reason, assessment of the BRAF V600E mutation in ameloblastomas might play a pivotal role in tumor management and could therefore soon become a routine test in clinical practice. 8 Molecular tests, such as DNA sequencing and polymerase chain reaction (PCR)-based assays, and immunohistochemistry are currently available for the detection of BRAF V600E mutation in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The role of BRAFv600e in ameloblastoma has gained clinical interest with the emergence of targeted therapy in the neoadjuvant setting 11–13 . Initial results from trials using targeted towards the BRAF gene have shown promising results in such selected cases of ameloblastoma, but there is currently a lack of prospective clinical trials evaluating the efficacy of targeted therapy in this disease 14 . While it is therefore plausible that the patients with BRAF‐v600e mutation positive ameloblastoma have a higher recurrence rate, these patients may benefit from combined surgical and targeted therapy against BRAF .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Initial results from trials using targeted towards the BRAF gene have shown promising results in such selected cases of ameloblastoma, but there is currently a lack of prospective clinical trials evaluating the efficacy of targeted therapy in this disease. 14 While it is therefore plausible that the patients with BRAF-v600e mutation positive ameloblastoma have a higher recurrence rate, these patients may benefit from combined surgical and targeted therapy against BRAF. The lack of widespread availability of targeted therapy limits routine diagnostic testing for this variant mutation in routine clinical practice.…”
mentioning
confidence: 99%